Cálculo del anticipo de impuesto a la renta con normativa vigente, caso Empresa Universitaria S.A. - Granda Benavides, Andrea Yaribel (My University, 2019)
In Ecuador, taxes play an important role as a source of income that contributes to the economic and social development of the nation, to become a progressive society. Thus, every person who carries out a commercial or business activity is obliged to pay taxes. Of the taxes that are collected in the country, the Income Tax is the second that generates more income and from this, the Income Tax Advance is made. Therefore, in the present case study, it seeks to determine the calculation of the Income Tax Advance, applying the current legal regulations. The research is carried out under the documentary-bibliographic research modality, which is based on the review of scientific articles and indexed journals; for the quality of information, it offers based on proven studies. In addition to the revision of the Tax Code, the Internal Tax Regime Law, the Regulations for the Application of the Internal Tax Regime Law and Executive Decree No. 806 issued by the Internal Revenue Service. For the advancement of research, the descriptive methodology for the development of the theoretical part has been chosen as a choice and with the support of the problematic method for the solution of the practical exercise. The results obtained in the calculation of the Advance of the Income Tax by means of the revision of the tax regulations; it was possible to verify that the company is exempt to the payment of the advance payment for being newly constituted.
En el Ecuador los tributos juegan un rol importante como fuente de ingresos que contribuyen al desarrollo económico y social de la nación, para convertirse en una sociedad progresista. Es así que, toda persona que realice una actividad comercial o empresarial está obligada a pagar impuestos. De los impuestos que se recauda en el país, el Impuesto a la Renta es el segundo que más ingresos generan y a partir de ello se realiza el Anticipo del Impuesto a la Renta; por consiguiente en el presente estudio de caso busca determina el cálculo del Anticipo de Impuesto a la Renta, aplicando las normativas legales vigentes. La investigación se desarrolla bajo la modalidad de investigación documental-bibliográfica, la cual se fundamenta en revisión de artículos científicos y de revistas indexadas; por la calidad de información que ofrece basados en estudios comprobados. Además de la revisión del Código Tributario, la Ley de Régimen Tributario Interno, el Reglamento para la Aplicación de la Ley de Régimen Tributario Interno y el Decreto Ejecutivo No. 806 emitida por el Servicio de Rentas Internas. Para el avance de la investigación se ha tomado como elección la metodología descriptiva para el desarrollo de la parte teórica y con el apoyo del método problemático para la solución del ejercicio práctico. Los resultados obtenidos en el cálculo del Anticipo del Impuesto a la Renta mediante la revisión de las normativas tributarias, se pudo constatar que la empresa se encuentra exenta al pago del anticipo por estar recién constituida.
Keywords: TRIBUTACIÓN; ANTICIPO DEL IMPUESTO A LA RENTA; SISTEMA TRIBUTARIO